LAND MONITORING IN AGRICULTURE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Agriculture is one of the key sectors of the economy in many countries. It ensures the food safety of the population and creates jobs for hundreds of thousands of people. However, effective management of agricultural land has become a serious problem in recent decades.Monitoring of agricultural lands allows you to determine the state of the soil, vegetation, water resources and other factors affecting the production capabilities of the earth.